Peran Auditor Eksternal dalam Memperkuat Akuntabilitas Keuangan UMKM pada Era Transformasi Digital di Indonesia - Nur Aliyah Rahma Saleh; Elis Oktaviani; Masyhuri, Masyhuri (Journal of Economics, Management, and Accounting, 2025)
This study analyzes the development of digitization and strengthening of the MSME financial system in Indonesia as an effort to improve transparency, accountability, and the quality of internal control. Based on national data from BPS, Kemenkop UKM, and OJK, it appears that technology adoption by MSMEs has shown significant improvement, particularly in the use of digital recording, cloud accounting, and involvement in the digital ecosystem. However, internal audit capabilities still face various obstacles, including limited financial literacy, a lack of understanding of technology, and unpreparedness in implementing more structured control procedures. These findings indicate that digitalization not only improves operational efficiency but also plays a strategic role in strengthening financial governance, which is the foundation for access to financing and long-term growth. Therefore, continuous support from the government, financial institutions, and other stakeholders is needed to accelerate technology adoption and strengthen internal audit capacity so that MSMEs can develop sustainably amid the dynamics of the digital economy.